PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF-EFFICACY MATEMATIS SISWA - Jannah S, Rauzatul; Fajriana, Fajriana; Mursalin, Mursalin; Ningtiyas, Fitri Ayu (Jurnal Pendidikan Matematika Malikussaleh, 2024)
This research is motivated by a problem, namely the low ability to solve mathematical and self-efficacy mathematical problems where the learning process is still centered on the teacher. Thus given a solution using the Creative Problem Solving (CPS) learning model aims to determine the improvement of mathematical problem solving capabilities and mathematical self-efficacy students using the Creative Problem Solving (CPS) learning model is better than students taught with conventional learning models. The research approach is in the form of quantitative. The type of research used is Quasi experiment with non-equivalent Control Group Design research design. The population in the study was all students of class VII MTsS Jabal Nur, while the sample was class VII-1 as the experimental class and class VII-2 as the control class chosen with purposive sampling technique. The data collection techniques used are instruments for the ability to solve mathematical problems and non self-efficacy mathematical questionnaire tests are divided into pretest and post-test. Data is processed using SPSS software version 18. Analysis of data conducted for the mathematical problem solving capability test using non-parametric tests (Mann Whitney U) because there is data that is not normally distributed. Asymp sig value, (2-tailed) is 0,000 <0.05, then  is rejected and  is accepted. Then for the analysis of students' mathematical self-efficacy questionnaires using the normality test, homogeneity. After the data is declared normal and homogeneous Furthermore, a hypothesis test with a significant value Ë‚ 0.05 is 0,000, then  is rejected and  is accepted. It can be concluded that the increase in mathematical problem solving capabilities and mathematical self-efficacy uses the Creative Problem Solving (CPS) learning model is better than students taught with conventional learning models in class VII MTsS Jabal Nur.